Design and automation of specific geometric quality controls for cone-radiosurgery treatments. (April 2022) - Doudard, A.; Guérin, C.; Dufreneix, S.; Josset, S.
Highlights: There is a lack of efficient integrated machine quality assurance tools when third-party systems are associated to the linac. A basic cone alignment test was developed for SRS cones. A Winston-Lutz test variant is suggested for the smallest cones. A cone alignment test is suggested as a pre-treatment QA for SRS treatments. Abstract: Purpose: The Varian TrueBeam STx linac can be equipped with BrainLAB stereotactic cones and ExacTrac imaging system for SRS treatments. However, these two third-party systems lack integration in a self-performance diagnosis tool dedicated to the SRS platform. The aim of this work was to design and automate essential geometric tests considering the complete set of cones with diameter range from 4 to 15 mm. Methods: EPID-based tests were focused on the cone alignment, the radiation isocentricity and the isocenters congruence. Images acquired with or without the BrainLAB pointer were analysed using the Hough transform and morphological filtering operations, after assessment of the algorithm accuracy using simulated images. The new Machine QA program was experimented over one year. Results: A subpixel resolution of 0.02 mm was found for the circular-field center detection algorithm. The tests results did not depend on the pointer location. The maximum deviations reported were in accordance with the AAPM SRS guidelines. The accurate localization of the linac radiation isocenter allowed for guidance of the ExacTrac calibration. A misalignment reaching 0.2 mm was measured for all cones but one, highlighting the benefit of systematizing this control before each patient SRS treatment. Conclusion: An effective in-house QA program dedicated to SRS cones was developed to supplement the standard machine performance check on our mixed SRS platform. Specific geometric tests even include the smallest 4-mm cone, which could be of great interest for future clinical indications such as the radiosurgery of functional disorders.